Strategy for Management and Procurement of Agility and Strength Training Equipment to Improve Athlete Performance at the Ps. Palas Football Development Center, Padang Lawas Regency, North Sumatra - Yusran Rizki; Amir Supriadi; Rahma Dewi (Universitas Negeri Semarang, 2025)
This study aims to analyze the management and procurement strategies for agility and strength training equipment in an effort to improve athlete performance at the PS. Palas Football Development Center in Padang Lawas Regency, North Sumatra. The main problem underlying this research is the limited training facilities and infrastructure, as well as the suboptimal strategy for managing and procuring training equipment that can support athlete achievement. This study uses a mixed methods research method with a sequential explanatory design, which begins with the collection and analysis of quantitative data through questionnaires, then continues with in-depth qualitative data through interviews and observations. The research subjects included 20 athletes, 5 coaches, and 5 club managers. The results show that the level of need for agility and strength training equipment is in the high category (85%), while the level of availability of facilities and infrastructure is still in the medium category (60%). Effective management strategies include planning training programs based on needs, optimal scheduling of equipment use, and routine equipment maintenance. Meanwhile, the procurement strategy is carried out with a collaborative approach through cooperation with local governments, sponsors, and local sports organizations. The implementation of this strategy has been proven to improve athlete performance, as indicated by a 20% increase in fitness test results and basic soccer technical skills after the program was implemented.